Jean Nicolas De Surmont. Chanson: son histoire et sa famille dans les dictionnaires de langue française - Jaques, François (Lexikos, 2010)
The fundamental aim of the study of the chansonnier vocabulary in French is to highlight the existence of a literary genre, namely the chanson. The author states that the chanson genre, as referred to in the Middle Ages, is characteristically French in view of the prestige of the French language and culture over centuries and the study thus comprises an analysis of the term chanson and its lexical family from its origins in old French to today’s modern French.